2018
DOI: 10.1016/j.foostr.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adding a commercial phytosterol ester mixture on the ‘equilibrium’ crystallization behavior of palm oil

Abstract: The objective of this study was to in depth investigate the 'equilibrium' state morphology and properties of crystals obtained after long-term isothermal crystallization and annealing of palm oil (PO) in the presence of different concentrations of phytosterol esters (PEs). A commercially available mixture of PEs was added to PO (0-100% PEs, 10% increment) and the effect of PE addition was analyzed with differential scanning calorimetry, X-ray diffraction, nuclear magnetic resonance, polarized light microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The β polymorph is identified by its characteristic peak at 4.6 Å for palm oil based samples, while the peaks at 3.9, 4.2, and 4.3 Å indicate the presence of a β ’ polymorphic form. [ 42–46 ] The β ’ form was dominantly present in the FB‐100 sample, as the peak at 4.6 Å was relatively small compared to the peak at 4.2 Å, which is the characteristic peak of β ’. Furthermore, the amount of β ‐crystals was the lowest in the pure sPMF sample (i.e., FB‐100) compared to the other three FBs, since the peak area of the peak at 4.6 Å was larger for the mixtures of sPMF and HOSO.…”
Section: Resultsmentioning
confidence: 99%
“…The β polymorph is identified by its characteristic peak at 4.6 Å for palm oil based samples, while the peaks at 3.9, 4.2, and 4.3 Å indicate the presence of a β ’ polymorphic form. [ 42–46 ] The β ’ form was dominantly present in the FB‐100 sample, as the peak at 4.6 Å was relatively small compared to the peak at 4.2 Å, which is the characteristic peak of β ’. Furthermore, the amount of β ‐crystals was the lowest in the pure sPMF sample (i.e., FB‐100) compared to the other three FBs, since the peak area of the peak at 4.6 Å was larger for the mixtures of sPMF and HOSO.…”
Section: Resultsmentioning
confidence: 99%
“…Restricting the movement of TAG molecules increases the nucleation time as a longer period is needed for sufficient TAG molecules to travel and pack onto the growing nucleus before it exceeds the critical size and become stable. This molecular restriction can be done by increasing the viscosity of the oil, [ 19,20 ] diluting the oil to increase the travelling distance, [ 21 ] and stearic hindrance of seeding molecules with TAG molecules preventing latter incorporation into the forming nucleus. [ 22 ] On the other hand, the formation of heterogeneous nuclei can decrease induction time as it is easier to form than homogenous nuclei of TAG.…”
Section: Crystal Formationmentioning
confidence: 99%
“…This effect was observed as an increase in induction time from 0.7 min to above 17.1 min when phytosterol ester concentration increases from 0% to 40% [ 38 ] and a linear decrease in SFC of the oil with an increased concentration of phytosterol ester. [ 21 ]…”
Section: Seeding Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results enabled research on the impact of adding PEs to PO under industrially more relevant crystallization conditions. More specifically we investigated the influence of PE addition on the 'equilibrium' crystallization state of PO in order to evaluate whether PE addition gives desired properties to the end product 15 . It was found that PE addition has a major influence on each level of the crystalline structural hierarchy (primary crystallization, polymorphism, network formation and textural properties).…”
mentioning
confidence: 99%